2011
DOI: 10.1111/j.1651-2227.2011.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal visual evoked potentials in preschool children born small for gestational age

Abstract: Our findings do not indicate any differences in VEP latency at preschool age for children born SGA compared with children born AGA. The results may support previous studies, suggesting that children born SGA show accelerated neurophysiologic maturation during their first year of life and that previously delayed VEP latencies after catch-up stay unchanged compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
3
10
2
Order By: Relevance
“…The present results are in agreement with those of several studies demonstrating decreased VEP amplitudes in preterm populations 8 24. We report normal latency, which was found in the same cohort at 5 years,3 in contrast to previous reports of delayed latencies in study groups at the ages of 4–6 years24 and 11 years 8. However, essential differences exist between our study and those of earlier ones, which included extremely preterm children,8 very low birthweight children8 and appropriate for gestational age children in their control groups,3 as opposed to the full-term controls used here.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present results are in agreement with those of several studies demonstrating decreased VEP amplitudes in preterm populations 8 24. We report normal latency, which was found in the same cohort at 5 years,3 in contrast to previous reports of delayed latencies in study groups at the ages of 4–6 years24 and 11 years 8. However, essential differences exist between our study and those of earlier ones, which included extremely preterm children,8 very low birthweight children8 and appropriate for gestational age children in their control groups,3 as opposed to the full-term controls used here.…”
Section: Discussionsupporting
confidence: 94%
“…We report normal latency, which was found in the same cohort at 5 years,3 in contrast to previous reports of delayed latencies in study groups at the ages of 4–6 years24 and 11 years 8. However, essential differences exist between our study and those of earlier ones, which included extremely preterm children,8 very low birthweight children8 and appropriate for gestational age children in their control groups,3 as opposed to the full-term controls used here. No correlations were found between the PRVEP variables and macular or papillary RNFL thickness.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…An ophthalmological substudy with focus on visual evoked potential (VEP) on these MLP children has previously been reported (Nilsson et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence is currently emerging that even near-term birth predisposes those children to a higher risk of mortality and morbidity than term infants (Engle et al 2007). To date, very few studies have focused on the ophthalmological aspects of this particular subset of children (Robaei et al 2006;Nilsson et al 2011). Previously, a relationship between birthweight (BW) and refraction at birth in both term and premature infants has been reported, weight being the better predictor than gestational age (GA) (Varghese et al 2009). Furthermore, a study from New Zealand showed an increased risk of strabismus and subnormal visual maturation in moderate prematurity and/or low BW compared with normal BW at 6 years of age (Robaei et al 2006).…”
Section: Introductionmentioning
confidence: 99%